2010
DOI: 10.1038/ajg.2010.287
|View full text |Cite
|
Sign up to set email alerts
|

Single-Center Experience With Drug-Induced Liver Injury From India: Causes, Outcome, Prognosis, and Predictors of Mortality

Abstract: Although drug-induced liver injury (DILI) is rare, it may result in signifi cant morbidity or death. The causes and outcome vary according to regions, with acetaminophen and complementary medicines common in the West and the Far East, respectively. This study evaluates the causes, outcomes, predictors, and models for 90-day mortality from DILI from India. METHODS:Consecutive patients with DILI from 1997 to 2008 based on International Consensus Criteria from a medical college hospital setting were studied. RESU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
190
5
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 208 publications
(224 citation statements)
references
References 41 publications
12
190
5
8
Order By: Relevance
“…29 Hy's law has been corroborated in several studies [18][19][20] including a recent single center study from India, which found a mortality of 21.5% in a setting where transplantation was not available. 9 Some drugs producing hepatotoxicity do not fit into a particular pattern, taking months and years of cumulative use to produce injury ( Table 2). Often they cause very minimal or no rise in liver enzymes.…”
Section: Patterns Of Drug-induced Liver Injurymentioning
confidence: 99%
See 3 more Smart Citations
“…29 Hy's law has been corroborated in several studies [18][19][20] including a recent single center study from India, which found a mortality of 21.5% in a setting where transplantation was not available. 9 Some drugs producing hepatotoxicity do not fit into a particular pattern, taking months and years of cumulative use to produce injury ( Table 2). Often they cause very minimal or no rise in liver enzymes.…”
Section: Patterns Of Drug-induced Liver Injurymentioning
confidence: 99%
“…In a single center study from India, DILI contributed to 1.4% of all gastrointestinal admissions and 2.5% of hepatobiliary admissions with a gradual increase in the numbers over the years. 9 In those presenting to the hospital with jaundice only a small minority of patients (0.7%) were due to idiosyncratic DILI. 10 The common drugs causing DILI appear geographical.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Our case describes altered mental status, hyperammonemia, deranged LFTs as the presenting signs of DILI distinguishing it from VHE. Early diagnosis and management of DILI is very important as it has high mortality ranging from 11.7% to 17.3% [25]. Due to the poor prognosis of DILI, clinicians must do a thorough work up in the patient taking VPA with altered mental status as it may be a sign of DILI and unrelated to hyperammonemia.…”
Section: Discussionmentioning
confidence: 99%